The Implementation Of Pie (Point, Illustration, Explanation) And Author’s Chair Strategy In Teaching Writing At The Tenth Grade Students Of Sman 18 Makassar - Jihad, Adriani (Jurnal Suluh Pendidikan, 2023)
The objective this research is to find out the improvement of students writing ability after being taught by using PIE and Author’s Chair strategy. This research used pre-experimental method. The population of this research was the tenth grade students of SMAN 18 Makassar. The sample was 22 students which were taken by using purposive sampling tehnique. The result indicated that the mean score of post-test was higher than pre-test (76.36>62.22) and t-test was greater than the value of t-table 13.205>2.080. It means that there was a significant difference between the students’ pre-test and post-test in teaching by using PIE and Author’s Chair strategy. It concluded that teaching writing by PIE and Author’s Chair strategy can improve students writing ability at the tenth grade students of SMAN 18 Makassar